Appendiceal Endometriosis With Intestinal Metaplasia Mimicking Low-Grade Appendiceal Mucinous Neoplasm. (21st September 2018) - Chen, Anne; Tabbara, Sana; Theisen, Brian
Abstract: Objectives: Intestinal metaplasia, defined by the presence of goblet cells, may rarely manifest in endometriosis. This may present a diagnostic dilemma when it involves the appendix, given the differential diagnosis of an appendiceal mucinous neoplasm at this location. We present the histologic and immunohistochemical findings of a cystic lesion involving the appendiceal wall that favored endometriosis with intestinal metaplasia. Methods: This is a case study of a 36-year-old woman with stage 4 endometriosis who underwent a hysterectomy and bilateral salpingo-oopherectomy for endometriosis debulking. Intraoperatively, appendiceal adhesions were noted and assumed to be endometriosis associated. As such, the decision for an appendectomy was made. Results: Grossly, the appendix specimen demonstrated no discrete lesions. Histology revealed a mucin-filled cystic structure confined to the appendiceal tip lined by endocervical-type epithelium with goblet cells and associated endometrial stroma. The entire appendix was submitted and revealed foci of traditional endometriosis within the appendiceal wall. Immunohistochemistry of the mucinous lesion was positive for CD10 and ER in the stroma and positive for CDX2 in the epithelium. A PAX8 highlighted the epithelium in the foci of traditional endometriosis and was negative in the epithelium of the mucinous cystic lesion. The accompanying hysterectomy and bilateral salpingo-oopherectomy specimen contained adenomyosis and bilateral ovarian endometriomas. Conclusion: The presence of endometrial stroma in association with this mucinous cystic lesion favors a diagnosis of endometriosis with intestinal metaplasia, despite the epithelial PAX8 negativity. This case is also unique in that the patient did not present with appendiceal symptoms or a discrete mass but was undergoing endometriosis debulking. An awareness of the possibility that endometriosis with intestinal metaplasia may involve the appendix and mimic an appendiceal mucinous neoplasm is important to avoid misdiagnosis and guide patient management.